CLAY HEADS AS NASCA TROPHY HEAD SUBSTITUTES - Hoffmann, Beatrix (2009)
The so called “heads are characterized trophy” be born represented in ceramics, proceeding from the south coast of Peru, to propose the possible function and meaning that fulfilled from the iconographic representations and comparisons with examples of other parts world. The author suggests that the heads trophy real and the representations of such heads were important in the world view; it was not necessary to use the first ones to fulfill the above mentioned functions, but symbols were used, you answer in clay and the corresponding paintings in funeral contexts like substitutes of the real ones. This way, since in other parts of the world there appears the complexity and changeability of the related ideas, the function is a difficult comprehension cabalmente and meaning of the heads trophy is born.